Reactive Power Control of PV Inverters in Active Distribution Grids with High PV Penetration - (:unkn) unknown (My University, 2023)
Photovoltaic (PV) systems can reduce greenhouse gas emissions while providing rapid reactive power support to the electric grid. At the distribution grid level, the PV inverters are controlled to reduce the system’s active power loss and to address problems caused by the PV systems themselves. For example, the distribution grid may face overvoltages due to high PV generation during off-peak hours. In this paper, a reactive power control approach for PV inverters is proposed to control the injection/absorption of reactive power to reduce the active power loss of the system while solving the overvoltage problem. To achieve this, the proposed controller periodically dispatches the reactive power setpoints and applies a real-time volt/var algorithm. The proposed method uses probabilistic distributions to account for the uncertainties in PV generation and load demand. The controller is implemented at the lateral level which simplifies the required communication platform and reduces the computational cost. The real-time volt/var control coordinates the operation of the different inverters during overvoltage conditions so that the voltage rise is limited using as little reactive power as possible by the inverters. Accordingly, the active power loss due to reactive power flow in the system is reduced. Two distribution systems are simulated using Open Distribution System Simulator (OpenDSS) and used to evaluate the proposed controller and compare with two other methods. A daily time series simulation is performed to test different operating conditions. The simulation results show that the proposed controller is able to reduce the active power loss in general and solve the overvoltage problem with a lower reactive power requirement than the other volt/var methods.
Keywords: Bilgisayar Bilimleri; Mühendislik ve Teknoloji; Computer Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; Mühendislik; Malzeme Bilimi; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; ENGINEERING; MATERIALS SCIENCE; Genel Bilgisayar Bilimi; Fizik Bilimleri; Genel Malzeme Bilimi; Genel Mühendislik; General Computer Science; Physical Sciences; General Materials Science; General Engineering; Distribution network; Inverters; Optimization; photovoltaic; power loss minimization; Reactive power; Reactive power control; Real-time systems; smart inverters; Surges; volt/var control; Voltage control